EFFECT OF CORAL GONIOPORA IN COMPARISON WITH CORAL APATITE TOWARDS HUMAN DENTAL PULP STEM CELLS MINERALIZATION ACTIVITIES: EFEK CORAL GONIOPORA DIBANDINGKAN DENGAN CORAL APATITE TERHADAP AKTIVITAS MINERALISASI SEL STEM PULPA GIGI - Rachmi Fanani Hakim; Endang Winiati Bachtiar; Nurtami Soedarsono (Dentika: Dental Journal, 2012)
Challenging approach in tissue engineering for dentin regeneration is focused upon the application of a scaffold on anopen pulp enabling odontoblast-like cells to grow into the scaffold and to convert them into dentin-like substance. Coralwas chosen as a scaffold because of its good biocompatibility and resorbability. The species of marine invertebratesexploited in medical applications are Members of Porites and Goniopora. Coral goniopora is most marine invertebratafound in Indonesia's marine. Coral apattite, an osteoconductive synthetic bone graft substitute material, is manufacturedby the hydrothermal conversion of the calcium carbonate skeleton of coral to hydroxyapattite in the presence ofammonium phosphate preserving the original porous structure which is similar to that of bone. The aim of study was toinvestigate the effect of Coral goniopora and coral apattite as a potential scaffold on dental pulp mineralization activity. Invitro DPSCs mineralization activity was measured by von Kossa staining for calcium deposit identification. The resultthat Coral apattite increased more calcium deposited identification than coral goniopora. Calcium deposited on dentalpulp stem cells are marker for mineralized dental pulp stem cells (DPSCs). Mineralized DPSCs are marker forodontoblast diferentiation and maturation. In conclusion, these observations demonstrated that co-cultured coral apattiteand DPSCs induced a better mineralization activity than those cultured with Coral goniopora.